Superplume in the Antarctic sector of the Pacific: position, genesis, age - Usenko, V. P.; Greku, R. Ch. (Ukrainian Antarctic Journal, 2019)
The study of the Earth structure and geodynamic is one of constitutive purposes of Earth sciences. The aim of our article is to describe Ross superplume that was discovered in the southwestern part of the Pacific Ocean near and under the western margin of Antarctica. This plume was not mentioned in seismic tomographic literature and in catalogs. Ross superplume was detected by gravimetric tomography method that was developed by Rudolf Greku in Institute of Geological Sciences, National Academy of Sciences of Ukraine. Authours used gravitomography data to describe the complex geometry of the superplume, evidences of the segmental collapse of the Paleo-Pacific slab (one of them to a depth of 4800 km), and its location within the pre-existing geothermal convective flow, under the influence of which the southwestern part of the Pacific Ocean, West Antarctica and the western part of East Antarctica are still located. Main conclusions. Combined effect of such factors as presence of geothermal interpolar flux and enter of slab into the outer liquid core within this flux led to formation of superplume. Two different parts of Ross superplume were formed in different structural-density conditions of lithospheric lower-mantle: the southern part was formed near and under the Antarctic obduction margin; the northern part was formed beneath the oceanic lithosphere. Ross superplume formation happened simultaneously with the 100 Ma event of the global reorganization of lithospheric structures, which drivers are poorly understood yet. We suppose that trigger of this event was explosive formation of Ross superplume. Our results were interpreted using available open literature data about this region and they do not contradict existing understanding of geodynamic history of the region.